PENGEMBANGAN INSTRUMEN TES ESSAY KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI LAJU REAKSI DI SMA/MA - Dwi Putri Liana; Jimmi Copriady; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to produce the essay test instrument critical thinking ability on the material reaction rate and know the validity and reliability of the test instrument. Research method using 4D model with four stages that is define, design, development, & disseminate, but done only until development stage (development). The test developed in the study consisted of fourteen items of essay referring to Ennis's critical thinking indicator of 10 indicators and the cognitive level of Bloom's Taxonomy C4-C5. The validation of the item is done by five validators with expert validity and content validity. Based on the validity according to the expert obtained average every aspect of the material 93,30%, construction 94,64% and language 92,29% with the average score of the overall validation of 93,41% has a valid category. While the content validity with Aikens formula obtained the average validation count of 0.92 categories is very good and all questions declared valid. Fourteen valid questions were tested for 30 students. The calculation of reliability coefficient (r11) with Alpha Cronbach formula obtained by 0.687 high category. The developed test instrument is considered valid and reliable so it can be used as a measuring tool to know the critical thinking ability of learners.Key word: Research & development, critical thinking test instrument,reaction rate